Mechanical and thermal activation of nickel-laterite mine waste as a precursor for geopolymer synthesis - Longos, Alberto L. (Animo Repository, 2020)
Geopolymer materials are increasing in scientific interest due to their flexibility in various applications. The geopolymer precursor is a mineral source with reactive Si and Al that is synthesized either mechanically or thermally to improve its cementitious activity. It was found out in previous literature that Nickel-laterite mine waste (NMW) is a prospective geopolymer precursor. However, this potentiality has not been explored in the Philippines, albeit the massive generation of NMW, which is merely dumped as a mining industry downstream process. This paper thus investigates the potential of the NMW as a raw material for geopolymer synthesis. Mechanical activation was performed using a ball mill with the following factors: ball-to-NMW ratio (4:1 and 10:1), mill speed (200 and 500 rpm), and grinding duration (30 and 120 minutes). Thermal activation was performed using a furnace treated at temperatures of 600, 700, and 800 °C. Response Surface Methodology (RSM) of the mechanical activation shows that a ball-to-NMW ratio of 10:1, mill speed of 443 rpm, and grinding duration of 120 minutes achieved optimized leachability of Si and Al. Thermal analysis results showed that NMW could be thermally activated from 600 to 800 °C. The results showed that both activation methods enhanced cementitious activity; hence, NMW could be utilized in geopolymer synthesis after thermal and mechanical activations. © 2020 The Author(s)